The effectiveness, safety and compliance of Zheng's supine rehabilitation exercise as a rehabilitation programme among elderly patients with AECOPD. (12th March 2020) - Lu, Haonan; Liu, Ni; Hu, Jie Ying; Wang, Xinni; Li, Youxia; Song, Mali; Zhong, Li Hong; He, Wei; Chen, RongChang; Zheng, Zeguang
Abstract: Purpose: We investigated the effectiveness, safety and compliance of Zheng's Supine Rehabilitation Exercise (ZSRE) as a rehabilitation programme among elderly patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Patients and methods: About 82 elderly patients with AECOPD were divided into a rehabilitation group and control group on their admission day, and both groups received routine medical treatment. Patients in the rehabilitation group started ZSRE on the second day of admission and continued until 8 weeks after discharge. Results: At the 9th week after discharge, the COPD Assessment Test (CAT), 6‐minute walking distance (6MWD) and Modified Medical Research Council Dyspnea Scale (mMRC) in the rehabilitation group were all significantly better than those in the control group ( P  < 0.01; P  < 0.01; and P  < 0.05, respectively). In the rehabilitation group, the CAT and 6MWD were significantly improved in the 9th week after discharge as compared with those at admission or discharge, and mMRC was significantly improved at the 9th week after discharge as compared with that at admission (all P  < 0.01). Conclusion: ZSRE can be performed by elderly patients with the acute exacerbation of severe or extremely severe COPD with high safety and compliance and was helpful for their recovery.